Peningkatan Kesadaran Masyarakat tentang Hipertensi melalui Edukasi dan Skrining di Dusun Cabean - Ashidiqi, Mahardhika Zulfa; Satritama, Ajar; Anggun Prima Jannata; Ananta, Ardian Surya; Putri, Cut Laras Dwi Hendia; Qur'aini, Farra Adina; Mukti, Laksono Hardi; Lestari, Putri Hayu; Fazaril A, Rasyad; Rosandia, Resita Nike; Meida, Nur Shani (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Hypertension is one of the non-communicable diseases that contribute to high mortality and health complications, especially in the elderly. Based on observations and discussions with community leaders and posyandu cadres, it was found that the incidence of hypertension in Cabean Hamlet is quite high. Therefore, this KKN program emphasizes hypertension counseling, elderly gymnastics, family care for people with hypertension, and balanced nutrition education as the main strategies in preventing and treating hypertension. The purpose of the Community Service Program (KKN) in Cabean Hamlet, Bumirejo, Lendah, Kulon Progo is to increase public awareness about hypertension so that it can reduce mortality and complications due to hypertension. The methods used in this program include educational approaches and hypertension screening. The educative approach was conducted through lectures and interactive discussions about hypertension and a healthy diet to prevent hypertension. Hypertension screening was carried out through blood pressure checks (which were carried out before and after the elderly gymnastics) and measurement of body weight and height.The results of the activity showed that there was an increase in public awareness about hypertension. The results of blood pressure checks showed a decrease in blood pressure in most participants after doing elderly exercises, with an increase in the percentage of blood pressure becoming normal (from 38.9% to 58.3%). In addition, in the family care program, two elderly people who were monitored showed different results, one had improved blood pressure after routinely taking antihypertensive drugs, while the other continued to have high blood pressure due to non-compliance with treatment. The results showed that there are still some residents with non-ideal nutritional status, both obese and malnourished, who are at risk of hypertension. In conclusion, the service-learning program succeeded in raising community awareness about hypertension and had a positive impact on lowering the blood pressure of the elderly through comprehensive interventions. The success of this program shows the importance of the role of family and community in supporting sustainable public health.